PERAN TIM PENDAMPING KELUARGA (TPK) DALAM PENURUNAN ANGKA STUNTING DI DESA BANDUNG BARU BARAT KABUPATEN PRINGSEWU - Laura Apriliana; Ayu Nadia Pramazuly; Hinfa Mosshananza (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
Stunting is a chronic nutritional problem that affects child growth. This study aims to determine the role of the Family Assistance Team (TPK) in reducing stunting rates in Bandung Baru Barat Village, Pringsewu Regency, as well as to identify the inhibiting factors in implementing this role. The government formed TPK to be involved in efforts to prevent stunting through education, assistance, and health service facilities. This research used a descriptive qualitative method with data collection techniques including interviews, observation, and documentation of key informants and supporting informants. Informants included members of the TPPS, TPK cadres, village midwives, and parents of stunted children. The research focuses on three indicators: the ideal role, the expected role, and the actual role. The results show that the implementation of TPK’s role has not fully met expectations due to various factors such as budget constraints, limited facilities, time availability of cadres, and lack of community participation. Therefore, the researcher suggests the need for capacity strengthening and increased support from the village government to ensure the TPK’s role can run optimally and sustainably. Keywords: Family Support Team (TPK); Stunting; Village